Estudo da atuação profissional dos egressos do curso de Mestrado em Ciência da Informação do IBICT, comparativamente à situação dos profissionais da informação na Inglaterra e Estados Unidos - Araujo, Esther Lück de (1982)
Analysis of the situation of the graduated students of the IBICT’s Master’s Course on Information Science verifying how this situation fits with the course’s objectives. A comparative study is carried out with similar surveys conducted in the United States and the United Kingdom. The professional situation is analyzed with aspects of: type of institution of employment, institutional sector where the professional operates and functions perform Is was found that professional activities performed by the graduates agree with the course’s established objectives he comparative study shows that there are differences in the situation of the information professionals among the countries evolved. Those differences being related to the social, political and economical context of each country, as well as the role played by scientific and technical information.